“Encontrando la voz”: análisis del uso de herramientas en procesos de reparación colectiva mediante grupos de escucha y expresión artística en habitantes de calle (Tema Central) - Cárdenas Méndez, Jean Paul (2025)
This project focused on the creation of a listening group—a safe and structured space where participants could share experiences, express emotions, and strengthen community bonds. Grounded in a human rights-based approach, the initiative employed Participatory Action Research (PAR) as its methodological framework, supported by a constructivist epistemology that views knowledge as a collective and contextually embedded process. The project prioritized dignity, horizontality, confidentiality, and the recognition and validation of each participant and their expressions. The sessions were thematically organized and addressed emotional regulation, identity reconstruction, stigma reduction, promotion of autonomy, and group cohesion, facilitating deep individual and collective reflection. Listening groups proved to be a key tool in collective reparation processes, enabling the acknowledgment of lived experiences, the strengthening of support networks, and the construction of a transformative narrative that disrupts social exclusion. Beyond addressing immediate needs, the project generated insights applicable to future programs and public policies aimed at addressing homelessness through an integral and rights-based lens. Each session was guided by a specific theme, ensuring meaningful contributions to participants’ processes of healing and empowerment.